B21 DNA vaccine expressing ag85b, rv2029c, and rv1738 confers a robust therapeutic effect against latent Mycobacterium tuberculosis infection - Weng, Shufeng; Zhang, Jinyi; Ma, Huixia; Zhou, Jingyu; Jia, Liqiu; Wan, Yanmin; Cui, Peng; Ruan, Qiaoling; Shao, Lingyun; Wu, Jing; Wang, Honghai; Zhang, Wenhong; et al. (Frontiers in Immunology, 2022)
Latent tuberculosis infection (LTBI) treatment is known to accelerate the decline in TB incidence, especially in high-risk populations. Mycobacterium tuberculosis (M. tb) expression profiles differ at different growth periods, and vaccines protective and therapeutic effects may increase when they include antigenic compositions from different periods. To develop a post-exposure vaccine that targets LTBI, we constructed four therapeutic DNA vaccines (A39, B37, B31, and B21) using different combinations of antigens from the proliferation phase (Ag85A, Ag85B), PE/PPE family (Rv3425), and latent phase (Rv2029c, Rv1813c, Rv1738). We compared the immunogenicity of the four DNA vaccines in C57BL/6j mice. The B21 vaccine stimulated the strongest cellular immune responses, namely Th1/Th17 and CD8+ cytotoxic T lymphocyte responses. It also induced the generation of strengthened effector memory and central memory T cells. In latently infected mice, the B21 vaccine significantly reduced bacterial loads in the spleens and lungs and decreased lung pathology. In conclusion, the B21 DNA vaccine can enhance T cell responses and control the reactivation of LTBI.